TEKNIK MARK PACKET DAN MARK CONNECTION UNTUK MANAJEMEN BANDWITH DENGAN PENDEKATAN TOP-DOWN - Sandy Kosasi (TECHSI - Jurnal Teknik Informatika, 2013)
The paper of this research is used for managing the user's wireless network that can be accessed using hotspot method in terms of improving the stability of internet access in accordance with the bandwidth capacity. This research applies mark packet and mark connection techniques to divide the available average bandwidth capacity and monitor the traffic data to support the needs of network service so that each client can work with the bandwidth capacity in accessing the internet. The form of this research is case study applying researchand development method and the techniques of data collection are in forms of observations, interviews, and documentation studies. This research applies NDLC (Network Development Life Cycle) method and uses Top-Down approach. The result of this research shows the ways of allocating the bandwidth numbers being available for each user to have stable and prevalent internet access and ease the operators in monitoring the users. In this case, the researcher uses Winbox as a software and Mikrotik OS as router and gateway in dividing the bandwidth